Hybrid energy storage systems for marine applications - Ma, Xin (2018)
Under the impact of the development of power electronics, ship propulsion technology has undergone tremendous changes, and it is imperative that electric propulsion would replace traditional diesel engine propulsion gradually. The introduction of energy storage technology into the ship power system can store excess energy when the ship is lightly loaded. In this way, it could prevent negative impact on the power supply when the ship load changes drastically and could provide energy for the load system during emergency conditions and special impulse load conditions. Since a single energy storage technology could not meet all requirements of various application modes, different energy storage technologies should be used in combination. In this dissertation, the author chose a hybrid energy storage system combined with battery and super capacitor to finish the function. The author designed a corresponding DC/DC converter to realize the fundamental simulation. Finally, based on the result of the simulation, an improved control method was developed. Keywords: Battery, Supercapacitor, Energy storage